Αξιολόγηση του ολοκληρωμένου εικονοσυστήματος τρισδιάστατης απεικόνισης V10 - Καμπούρης, Αναστάσιος-Γραμματάς (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Τοπογραφίας. Εργαστήριο Γενικής Γεωδαισίας, 2015)
The object of this thesis is the assessment of the three-dimensional integrated camera system V10 imaging rover on the implementation of geodetic surveys. The exploration of this new technology and methodology is being conducted within the framework of scientific check and research. This thesis aims to determine the general use of the system, the applications it is capable of accomplishing and its performance respectively. Furthermore, the V10 imaging rover is being contrasted with different methodologies and equipment. This thesis is summarized by the following five chapters: • The first chapter refers to the needs and reasons for the development of geometric documentations to natural formations and technical structures. Alongside a short overview of the different collecting methods for the three-dimensional information are presented as well as a brief review of the evolution of photogrammetric and geodetic instrumentation. • The second chapter presents analytically all the technical features of the V10 imaging rover and its operation principles. In addition, an in depth reference to both the field and office software of the system is reported, along with the capabilities they offer for the conduction of the survey. • The third chapter describes the calibration process that is carried out by the manufacturer as long as the laboratory calibration process which was conducted for two of the 12 digital cameras of the V10 camera head. The experiment took place in an indoor and an external 3D calibration fields which are sighted in the school of rural and surveying engineering, for the justification of the camera’s metering ability. • The fourth chapter presents in detail all the geodetic applications that were carried out with the V10 imaging rover and involved in surveying and documenting: - a building facade - a part of a monument - a vertical cylindrical fuel storage tank. These applications took place in parallel with different methods and equipment so as to compare their geometric derivatives and deliverables. • The fifth chapter summarizes all the final conclusions and deductions of the overall use of the V10 imaging rover as well as some suggestions and proposals about issues that were considered to be in the need of further exploration. Therefore the V10 imaging rover is particularly user-friendly and provides speed, stability and accuracy respectively. At the same time it is able to significantly reduce the time of field work although, there is an increase in the necessary reference stations and office work time. The geometric derivatives of the V10 in compliance with its essential qualifications can be used to construct three-dimensional models and diagrams of horizontal and vertical sections with a maximum print scale of 1:50. The accuracy that is being provided for the measurements of geodetic coordinates in an optimized process is of the order of ± 1cm. Finally, the stability of the geometric data of V10 enables the statistical processing of it. So by adjusting measured points on a circumference with nominal radius value of 11.5m, according to the necessary statistical tests, the V10 was able to measure it with an uncertainty of only ±5mm.